Haematological Changes in Hepatitis C (HCV) Patients - Qurrat Ul Ain, Huda Zameer, Amber Haroon, Sidra Kadir, Neelam Mazhar, Talha Laique, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Hepatitis C virus infection victimizes around 200 million people globally. Aim: To evaluate the frequency of haematological abnormalities in HCV infected patients. Study design: Cross Sectional study. Methodology: Present study with chronic HCV infection was carried out in the Department of Pathology, CMH, Multan after the Hospital’s Ethical Committee approval. All patients (n=175) of HCV positive on ELISA were further investigated with hematological parameters. Venous blood was send to laboratory for complete blood count (CBC). The outcome variables i.e. hematological abnormality as (Yes/No), duration or hepatitis C infection, personal data like age, gender, living area and occupation were noted on the Performa. Statistical analysis: SPSS software, version, 26 analyzed the collected data. Results: All patients (n=139) had a mean age of 32.46 ± 7.35years. In frequency of gender of patients there were 101(57.71%) males and 74(42.29%) females. Mean TLC was 11.43±1.33 x 103µL. Mean Hb% was 10.57±3.41 g/dl. Mean platelet count was 154.27± 25.45 x 103 µL. Frequency of haematological abnormalities in HCV infected patients was found in 47 (26.86%) patients. Conclusion: We concluded that the frequency of haematological abnormalities in HCV infected patients is quite high.